The Link Between Cannabis Use and Violent Behavior in the Early Phase of Psychosis: The Potential Role of Impulsivity - Moulin, Valerie; Framorando, David; Gasser, Jacques; Dan-Glauser, Elise (Frontiers in Psychiatry, 2022)
Introduction Recently, the literature has shown that Cannabis Use (CU) was a risk factor for Violent Behavior (VB) in patients with psychosis, and those in the early phase of psychosis (EPP). These findings are relevant because of the high prevalence of CU in this EPP, and the potential for prevention during this phase of illness. However, there is still a lack of clear explanations, supported by empirical evidence, about what underlies the link between CU and VB against other. Method This viewpoint reviews the scientific literature on the link between CU and VB, and the involvement of impulsivity in this relationship. This last point will be addressed at clinical and neurobiological levels. Results Recent studies confirmed that CU is particularly high in the EPP, and is a risk factor for VB in the EPP and schizophrenia. Studies have also shown that impulsivity is a risk factor for VB in psychosis, is associated with CU, and may mediate the link between CU and VB. Research suggests a neurobiological mechanism, as CU affects the structures and function of frontal areas, known to play a role in impulsive behavior. Conclusion Scientific evidence support the hypothesis of an involvement of impulsivity as a variable that could mediate the link between CU and aggression, particularly, when CU has an early onset. However, this hypothesis should be confirmed with longitudinal studies and by taking into account confounding factors. The studies highlight the relevance of early prevention in the EPP, in addition to interventions focusing on psychotic disorders.